2022
DOI: 10.1111/clr.13994
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive treatment of peri‐implant defects—Results after three and five years

Abstract: Peri-implantitis is a complication following implant therapy affecting soft and hard tissues around dental implants (Berglundh et al., 2018). In a recent systematic review and meta-analysis, the estimated weighted mean prevalence of peri-implantitis at a patient level was reported to be 22% (CI: 14%-30%) (Derks & Tomasi, 2015). Due to significant heterogeneity in case definitions, peri-implantitis prevalence in the included individual studies varied between 1% and 47%. Treatment of peri-implantitis is difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…When adjusting for the number of implants treated per subject, Aghazadeh et al (2012) indicated a higher likelihood (3.2) of success (defined as PPD ≤ 5 mm, allowing one site with BOP, no SOP at any implant surface, and gain or no loss of alveolar bone) at 12 months when DBBM rather than autologous bone were combined with a collagen membrane to treat peri‐implantitis defects. This trend was also confirmed at 5 years, when 36% of patients treated with autologous bone compared to 78.3% of patients treated with DBBM showed a successful outcome (Aghazadeh et al, 2022). Conversely, Regidor et al reported similar disease resolution (defined as no BOP/SOP, PPD ≤ 5 mm, and recession ≤1 mm) when DBBM was associated or not with a native collagen membrane (Regidor et al, 2023).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…When adjusting for the number of implants treated per subject, Aghazadeh et al (2012) indicated a higher likelihood (3.2) of success (defined as PPD ≤ 5 mm, allowing one site with BOP, no SOP at any implant surface, and gain or no loss of alveolar bone) at 12 months when DBBM rather than autologous bone were combined with a collagen membrane to treat peri‐implantitis defects. This trend was also confirmed at 5 years, when 36% of patients treated with autologous bone compared to 78.3% of patients treated with DBBM showed a successful outcome (Aghazadeh et al, 2022). Conversely, Regidor et al reported similar disease resolution (defined as no BOP/SOP, PPD ≤ 5 mm, and recession ≤1 mm) when DBBM was associated or not with a native collagen membrane (Regidor et al, 2023).…”
Section: Resultsmentioning
confidence: 80%
“…When focusing on RCTs included in FQ1, four raised some concerns in one domain (predominantly due to bias in measurement of the outcome) (Jepsen et al, 2016; Renvert, Roos‐Jansaker, & Persson, 2018; Renvert et al, 2021; Derks et al, 2022), while three studies were considered at high risk of bias, mainly due to the combination of missing outcomes and bias in selection of the reported results (Wohlfahrt et al, 2012; Isehed et al, 2016; Andersen et al, 2017; Isehed et al, 2018; Emanuel et al, 2020) (Figure 2 and Appendix S15). Among the RCTs included in FQ2, two were at high risk (Rakasevic & Gabric, 2021; Regidor et al, 2023), two raised some concerns (Aghazadeh et al, 2012; Aghazadeh et al, 2020; Polymeri et al, 2020; Aghazadeh et al, 2022), and one was at low risk of bias (Isler et al, 2018; Isler et al, 2022) (Figure 3 and Appendix S16). In particular, the domains related to the randomization process raised some concerns in 60% of the studies, while the domains related to missing outcomes and selection of the reported results raised concerns in 40% of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The follow-up periods among the included studies varied from 12 months (two RCTs) 18,19 to 3 years (1 RCT), 20 4 years (1 prospective study), 21 and 5 years (one prospective study and one RCT) 22,23 (Table 1). Two 2-arm studies compared different GBR-supported treatment approaches, 20,23 and four studies assessed the efficacy of the GBR-supported treatment protocol versus the application of bone substitute alone (i.e., synthetic particulated bone filler, 21,22 allogenic cortical bone embedded in demineralized fibers, 22 or xenogenic bone embedded in collagen matrix 19 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[19][20][21][22] All but one study reported on initial nonsurgical interventions prior to surgical therapy, including oral hygiene instructions and suband/or supra-mucosal instrumentation (Table 2). With respect to the protocols implemented for implant surface decontamination, the majority of the studies used a combination of mechanical debridement with titanium or plastic curettes and irrigation with physiological solution with 22,23,25 or without 20 adjunctive application of hydrogen peroxide (3%). Two studies used titanium brushes for mechanical removal of the biofilm from implant surfaces alone or with subsequent irrigation with hydrogen peroxide (3%) and saline.…”
Section: Study Characteristicsmentioning
confidence: 99%